PENINGKATAN KETERAMPILAN MENULIS CERITA PENDEK DENGAN COOPERATIVE LEARING PADA SISWA KELAS XI IPA 1 SMAN 3 METRO - Koryati, Wiwik Dwi (LPPM STKIP PGRI Bandar Lampung, 2020)
Write to teach students XI IPA 1 SMAN 3 Metro to short story. Rearange short story students reveal environments form see, listen, and felt. Write short story by topic ;see, listen, be kissed, be sampled, and felts. Research purpose: implimcation of method cooperative learning to students XI IPA 1 to write short story. Research method :observation, documents, and interview. Techniqe of data tes and non tes. Analysis data be analysis data, prepared data, and conclusions. The result: pracyclus 198, cyclus I 262, increased 64%, achievement learning pracyclus 53, cyclus I 69, increaswd 16%. Cyclus II write skill short story 295, increased 32%, achievement learning 79, increased 10%. Cyclus III write skill short story 308, increased 14%, and achievement learning 88, increased 9%. Conclusion: Cooperative learning of method to increased students XI IPA 3 SMAN 3 Metro write short story.